Dampak Penyaluran Infak Untuk Kegiatan Usaha Produktif dalam Penguatan Modal dan Peningkatan Kenerja UMKM - Muhammad Akbar Rafdison; Muhammad Nafik (Jurnal Ekonomi Syariah Teori dan Terapan, 2018)
This research aims to find out how the impact of infaq distribution productively affects reinforcement of capital and UMKM performance. Subject of UMKM that becomes an informant in this research is members of Guided Independent Business Group of Social Fund Foundation AlFalah Surabaya. This research uses qualitative approach with a case study strategy. Then, technique of collecting data uses interview directly to the objects, and technique of validating data uses source triangulation, while technique of analyzing data uses narrative-descriptive.       The result of this research shows that infaq fund distribution for productive activity that has been given by Social Fund Foundation Al-Falah could increase UMKM capital structure and impact to improving performance from the business that they manage. The last impact that they felt is there is business revenue increase, so that the UMKM subject could fulfill all the neccessities of life and improve the prosperity. REFERENCESAdnan, Muhammad Akhyar & Shochrul Rohmatul Ajija. 2015. The effectiveness of Baitul Maal wat Tamwil in reducing poverty: The case of Indonesian Islamic Microfinance Institution. Humanomics, Vol 31 lss: 2, 160-182.Hafidhuddin, Didin. 2002. Zakat Dalam Perekonomian Modern. Jakarta: Gema InsaniJakarsih, Aan. 2008. Pengaruh Kemampuan Manajerial Pengusaha Terhadap Keberhasilan Usaha pengusaha Sepatu di Sentra Industri Kecil Persepatuan Cibaduyut. Disertasi Tidak Diterbitkan. Bandung FPIPS UPI.Lembaga Zakat. 2001b. Zakat dalam Al-quran dan Hadist: Ayat-Ayat Al-Quran dan Hadits tentang Zakat Infaq dan Shadaqah, Jurnal Menggugah Nurani Menebar Peduli. Tanggal 29 Oktober 2001.Mahsun, Muhammad. 2006. Pengukuran Kinerja Sektor Publik. Yogyakarta: BPFE.Qardhawi, Yusuf. 1995. Kiat Islam Mengentaskan Kemiskinan. Jakarta: Gema Insani PressQardhawi, Yusuf. 2005. Spektrum Zakat Dalam Membangun Ekonomi Kerakyatan, Kajian Ekonomi Islam, Telaah Teoritis dan Praktisasi Sistem Syariah. Jakarta: Zikrul HakimRyandono, Muhammad Nafik Hadi. 2008. Ekonomi ZISWAQ (zakat, infaq, shadaqah, dan waqaf). Surabaya: Islamic Finance Development Institute (IFDI) dan CenforisSudarsono, Heri. 2008. Bank dan Lemabaga Keuangan Syariah Deskripsi dan Ilustrasi. Edisi Ketiga. Yogyakarta: Ekonosia.Sudewo, Eri. 2004. Manajemen Zakat. Jakarta: Institut Manajemen ZakatSuhendra, K. 2006. Peranan Birokrasi Dalam Pemberdayaan. Bandung: AlfabetaSoemitra, Andri. 2009. Bank dan Lembaga Keuangan Syariah. Jakarta: Kencana Prenada Media GroupYin, Robert. 2002. Studi Kasus Desain dan Metode. Jakarta: PT Raja Grafindo PersadaZadjuli, S. Imam. 2006d. Reformasi Ilmu Pengetahuan dan Pemberdayaan Sumberdaya Manusia. Makalah disampaikan dalam Temu Alumsi Sekolah Tinggi Agama Islam Negeri (STAIN) Ponorogo, Jawa Timur, Tanggal 8 Juli 2006.